Cold sintering of ceria-based solid electrolyte with the assistance of a core-shell structure. (December 2022) - Shen, Hui-Zhen; Guo, Rui; Guo, Ning; Shen, Ping
Abstract: Due to its strong ionic conductivity, doped ceria has been employed as an electrolyte in medium-temperature solid oxide fuel cell applications. For the first time, we demonstrated the feasibility of cold sintering high-density Ce0.8 Sm0.2 O1.9 (SDC)@Na2 CO3 composite electrolytes with Na2 CO3 as a shell at temperatures less than 200 °C. The effects of Na2 CO3 and water content on cold-sintered samples' relative density, microstructure, and ionic conductivity were examined. The core-shell structure is significant in densification, but water addition has an opposite effect. The bulk and grain-boundary conductivities of cold-sintered SDC@Na2 CO3 electrolytes were studied at 350−700 °C and analyzed in detail based on carbonate and water effects. This work presents a significant and scalable method for synthesizing dense solid electrolytes by forming a core-shell structure by cold sintering. Graphical abstract: Image, graphical abstract